The Role of Veillonella in The Pathogenesis of Periodontitis: Systematic Review - Soekanto, Sri Angky; Djais, Ariadna Adisattya; Theodorea, Citra Fragrantia; Sastradipura, Dewi Fatma Suniarti; Rohmah, Devi Kartika (FKG Universitas Syiah Kuala, 2025)
Veillonella is a common species found in the human oral cavity that plays a significant role in biofilm ecology. Veillonella is known to play a supporting role in colonizing other, more pathogenic species. Its abundant presence in supra- and sub-gingival biofilms is thought to have an associated relationship with red-complex bacterial species. These bacteria are known to be the causative of periodontal disease. Their ability to establish this mutualistic relationship is an important factor that we need to know to expand our understanding of their relationship to the pathogenesis of periodontal disease and to develop more effective treatments.